2023
DOI: 10.3847/1538-3881/acebdd
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Clouds in a Section of the Third Galactic Quadrant: Observational Properties and Chemical Abundance Ratio between CO and its Isotopologues

Chen Wang,
Haoran Feng,
Ji Yang
et al.

Abstract: We compare the observational properties between 12CO, 13CO, and C18O and summarize the observational parameters based on a 7069-cloud sample from the Milky Way Imaging Scroll Painting CO survey in a section of the third Galactic quadrant. We find that the 13CO angular area ( A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The means of fractions are about 15.6%, 18.8%, and 16.9%, for 12 CO, 13 CO, and C 18 O, respectively. Figure 6 is in line with the results of Wang et al (2023), who found an excellent correlation between 12 CO and 13 CO emissions, as demonstrated in Figure 12 therein. They derived a value of 0.13 for the ratio of 13 CO to 12 CO emissions, close to the mean flux fraction of the second exponential component revealed by the 12 CO flux-intensity relation.…”
Section: Multiline Flux-intensity Relationsupporting
confidence: 90%
See 1 more Smart Citation
“…The means of fractions are about 15.6%, 18.8%, and 16.9%, for 12 CO, 13 CO, and C 18 O, respectively. Figure 6 is in line with the results of Wang et al (2023), who found an excellent correlation between 12 CO and 13 CO emissions, as demonstrated in Figure 12 therein. They derived a value of 0.13 for the ratio of 13 CO to 12 CO emissions, close to the mean flux fraction of the second exponential component revealed by the 12 CO flux-intensity relation.…”
Section: Multiline Flux-intensity Relationsupporting
confidence: 90%
“…Similar to the total flux of molecular clouds, the flux of the second exponential component, F exp 2 , also scales up with the angular area, as demonstrated in panel (c) of Figure 4. F exp 2 occupies about 15.6% (the mean of all double-exponential clouds) of the total flux, very close to the flux ratio (about 13%) of 13 CO/ 12 CO found by Wang et al (2023).…”
Section: Flux-intensity Relations and Molecular Cloud Propertiessupporting
confidence: 81%
“…The typical excitation temperature of the gas is 8 ± 1 K (assuming the beam filling factor is 1 for these distant MCs at about 5-8 kpc) according to the peak emission of the 64 large 12 CO structures. More than 70% of samples in the 64 MCs have a relatively small 13 CO-to-12 CO intensity ratio (i.e., I( 13 CO)/I( 12 CO)∼0.1), which is roughly half the value of the normal MCs in the Galactic plane (∼0.2 in previous studies; see e.g., Tokuyama et al 2019;Wang et al 2023). We also find that the closer the MCs in the WGL are to the GC, the greater the velocity dispersion they have.…”
Section: Molecular Gas Flowing Toward the Cmz Along The Near Dust Lanementioning
confidence: 82%
“…This suggests a connection between high-temperature, high-density gas and star-forming activities in the Mon OB1 region. Actually, some studies also suggest that MCs with high T peak (>10 K, corresponding to T ex >13.4 K, Wang et al 2019Wang et al , 2023b or high column density (e.g., Wang et al 2023b) may be related to possible starforming activities.…”
mentioning
confidence: 99%